Koumine Attenuates Neuroglia Activation and Inflammatory Response to Neuropathic Pain - Gui-Lin Jin; Sai-Di He; Shao-Mei Lin; Li-Mian Hong; Wan-Qing Chen; Ying Xu; Jian Yang; Su-Ping Li; Chang-Xi Yu (Neural Plasticity)
Despite decades of studies, the currently available drugs largely fail to control neuropathic pain. Koumine—an alkaloidal constituent derived from the medicinal plant Gelsemium elegans Benth.—has been shown to possess analgesic and anti-inflammatory properties; however, the underlying mechanisms remain unclear. In this study, we aimed to investigate the analgesic and anti-inflammatory effects and the possible underlying mechanisms of koumine. The analgesic and anti-inflammatory effects of koumine were explored by using chronic constriction injury of the sciatic nerve (CCI) neuropathic pain model in vivo and LPS-induced injury in microglia BV2 cells in vitro. Immunofluorescence staining and Western blot analysis were used to assess the modulator effect of koumine on microglia and astrocyte activation after CCI surgery. Enzyme-linked immunosorbent assay (ELISA) was used to evaluate the levels of proinflammatory cytokines. Western blot analysis and quantitative real-time polymerase chain reaction (qPCR) were used to examine the modulator effect of koumine on microglial M1 polarization. We found that single or repeated treatment of koumine can significantly reduce neuropathic pain after nerve injury. Moreover, koumine showed inhibitory effects on CCI-evoked microglia and astrocyte activation and reduced proinflammatory cytokine production in the spinal cord in rat CCI models. In BV2 cells, koumine significantly inhibited microglia M1 polarization. Furthermore, the analgesic effect of koumine was inhibited by a TSPO antagonist PK11195. These findings suggest that the analgesic effects of koumine on CCI-induced neuropathic pain may result from the inhibition of microglia activation and M1 polarization as well as the activation of astrocytes while sparing the anti-inflammatory responses to neuropathic pain.